Teaching-learning methodology for formal languages and automata theory - De Souza, Gabriel Spadon [UNESP]; Olivete, Celso [UNESP]; Correia, Ronaldo Celso Messias [UNESP]; Garcia, Rogério Eduardo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Formal languages and automata (FLA) theory have fundamental relevance to the base of knowledge in the computer science area, especially focusing on scientific education. Usually presented by a discipline, the teaching-learning process of FLA is characterized by the high level of abstraction, and it is considered difficult due to the complexity of language formalisms. As support for the learning process, tools have been used to simulate language formalisms. However, the simulation is not enough to reinforce the construction of an abstract concept. In this paper, we present an FLA teaching-learning methodology based on the development of simulators as an approach to clarify the formalism for the students. Through developing their simulators, students are exposed to the data structure and algorithms to handle the formalism. Consequently, students have the opportunity to make the concept concrete.
Keywords: Cognitive Load; Computing; Education; Formal Language and Automata Theory; Learning Tool; Methodology; Visualization